2008
DOI: 10.1089/aid.2007.0213
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Genotypic Resistant Pattern in HIV-Infected Women and Children from Rural West Cameroon

Abstract: The distribution of antiretroviral (ARV) therapy resistance mutations among HIV-1 strains was evaluated in 39 postpartum women, one pregnant woman, and 12 HIV-positive babies (seven newborns and five children) living in rural west Cameroon. Thirty-five women and all newborns received a single dose of nevirapine (NVP) to prevent mother-to-child transmission of HIV-1; two women were ARV treated and three were ARV naive. Of the 52 viral strains examined, three were subtype B, 45 were classified into eight HIV-1 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
2
5
0
Order By: Relevance
“…9 Our findings suggest that the exposed children had developed resistance mutations to nevirapine, mainly K103N, Y181C, and G190A, as has been demonstrated in studies on resistance in infants following single-dose nevirapine exposure. [2][3][4][5][12][13][14][15][16][17][18] We did not find a difference between the rates of virologic suppression in the exposed children who started an NNRTIcontaining regimen within 6 months of exposure to perinatal single-dose nevirapine and the exposed children who started the NNRTI-containing regimen after 6 months of exposure to single-dose nevirapine, as in previous reports. 9,19 Our results may be explained by the small numbers in our subanalysis, which may not have given us the required power to detect the differences.…”
Section: Discussionsupporting
confidence: 80%
“…9 Our findings suggest that the exposed children had developed resistance mutations to nevirapine, mainly K103N, Y181C, and G190A, as has been demonstrated in studies on resistance in infants following single-dose nevirapine exposure. [2][3][4][5][12][13][14][15][16][17][18] We did not find a difference between the rates of virologic suppression in the exposed children who started an NNRTIcontaining regimen within 6 months of exposure to perinatal single-dose nevirapine and the exposed children who started the NNRTI-containing regimen after 6 months of exposure to single-dose nevirapine, as in previous reports. 9,19 Our results may be explained by the small numbers in our subanalysis, which may not have given us the required power to detect the differences.…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, incomplete suppression of viral replication promotes the development of broader drug resistance, compromising subsequent treatment regimens. A number of studies have evaluated rates of resistance mutations in recently transmitted virus by looking at subjects with primary infection (28,29,32,33). Reported rates of drug resistance in these studies vary from 1.4 to 37.0% with most of the resistance mutations seen in the RT gene (23,27,31,(34)(35)(36)(37)(38)(39)(40).…”
Section: Introductionmentioning
confidence: 99%
“…In a study from Yaounde, Cameroon it was reported that 2.6% protease drug resistance and 9.3% major reverse transcriptase drug resistance were detected among patients who never received therapy, a finding that has implications for the efficacy of first line therapies [5]. Further in a study conducted at Doula, Cameroon [6] out of 819 patients who received first line ART, 36% had virological failure after 6 months or more. About 80% of drug resistance was detected for Nucleoside Reverse Transcriptase Inhibitors (NRTI) class, followed by the non-nucleoside reverse transcriptase Inhibitors (NNRTI) (76%) and Protease Inhibitor (PI) class (19%) drugs.…”
Section: Introductionmentioning
confidence: 99%